Card emulator for door access using android platform - Teck, T.Y. (2013)
This paper describes the communication protocols and programming flow that have been implemented in the development of a Card Emulator for Door Access Using Android Platform'. The launching of Google Wallet in 2011 has triggered the idea of industry to fully exploit the advantage of Android platform in our daily life. Thus, the main idea of this project is to develop a hardware sleeve which eventually will be utilised to replace the conventional key in security access through certain door or building. The communication protocols involved in this project are Bluetooth Serial Port Profile (SPP), Universal Asynchronous Receiver / Transmitter (UART) and Near Field Communication (NFC). Â© 2013 IEEE.